PETROGLYPHS OF THE GAVASAY BASIN - Anarbayev A. A.; Oynazarov G. X; Bekmirzayev I. I. (TARIXIY TADQIQOTLAR, 2025)
This article presents the results of survey and research conducted in the G‘ovasoy Valley, where petroglyphs scattered across the foothills of the upper part of the valley were discovered. According to the findings, more than 300 individual figures were recorded on a total of 52 rock surfaces. Their subjects, compositional features, techniques of execution, analogies, and chronology have been analyzed and introduced into scholarly circulation. These petroglyphs hold significant scientific value for studying the processes of anthropogenic landscape formation and the historical dynamics of ancient cultural layers in the G‘ovasoy Valley. The identification and investigation of such rock-carved monuments – widely distributed across Uzbekistan—within the G‘ovasoy Basin not only expand their overall number but also considerably broaden their known geographical range.